2004
DOI: 10.1086/382504
|View full text |Cite
|
Sign up to set email alerts
|

Star Clusters in the Galactic Anticenter Stellar Structure and the Origin of Outer Old Open Clusters

Abstract: The Galactic Anticenter Stellar Structure (GASS) has been identified with excess surface densities of field stars in several large area sky surveys, and with an unusual, string-like grouping of five globular clusters. At least two of these are diffuse, young "transitional" clusters between open and globular types. Here we call attention to the fact that four younger open or transitional clusters extend the previously identified, string-like cluster grouping, with at least one having a radial velocity consisten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 24 publications
5
122
1
Order By: Relevance
“…From this point of view Pal 1 is like thin disk stars and Open Clusters, but markedly different from thick disk stars, which show enhanced α to iron ratios (Fuhrmann 2008, and references therein). Note however, that from the data of Fuhrmann (2008), at the metallicity of Pal 1 the thin disk already displays an α element enhancement, [Mg/Fe] ∼ +0.2.…”
Section: Pal 1 As a Galactic Clustermentioning
confidence: 93%
See 1 more Smart Citation
“…From this point of view Pal 1 is like thin disk stars and Open Clusters, but markedly different from thick disk stars, which show enhanced α to iron ratios (Fuhrmann 2008, and references therein). Note however, that from the data of Fuhrmann (2008), at the metallicity of Pal 1 the thin disk already displays an α element enhancement, [Mg/Fe] ∼ +0.2.…”
Section: Pal 1 As a Galactic Clustermentioning
confidence: 93%
“…In particular, association of Pal 1 with the "GASS" (Galactic Anticenter Stellar Structure. Crane et al 2003;Frinchaboy et al 2004) and the controversial Canis Major dSph galaxy (Momany et al 2006;Martin et al 2004;Forbes & Bridges 2010) have been proposed. Association with the "orphan stream" (Belokurov et al 2007) was also suggested, although a recent study of the stream orbit argue against this possibility (Newberg et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mon, like Sgr, appears to have at least four globular clusters (C03). However, unlike Sgr, Mon also seems to contain younger star clusters that have traditionally been categorized as either MW 'old open clusters' or 'transitional clusters' between the open and globular classes (Frinchaboy et al 2004). The weight of evidence seems to favour Mon as a tidally disrupting dwarf galaxy with extensive debris arms like the Sgr system, as previously discussed by Y03.…”
Section: Other M-giant Tidal Streamsmentioning
confidence: 99%
“…Its intermediate-age, ∼3.5 Gyr, and low metallicity, [Fe/H] ∼ −0.4, (e.g. Tosi et al 2004;Bragaglia et al 2005) match within the framework of Galactic evolution, despite the suggestion by Frinchaboy et al (2004) that Berkeley 29 is associated with the Canis Major overdensity. Because Berkeley 29 is a very interesting object, we have included it in our sample despite the low number of stars selected as members in comparison to the other systems analysed with the exception of NGC 7789.…”
Section: Berkeley 29mentioning
confidence: 94%